Pan-Canadian standards for severe asthma in electronic medical records. Issue 6 (2nd November 2021) - Lougheed, M. Diane; Morra, Alison; Bullock, Emma; Tregobov, Noah; Barber, Dave; Boulet, Louis-Philippe; Dell, Sharon; Ducharme, Francine M.; Ferrone, Madonna; FitzGerald, J. Mark; Gupta, Samir; Licskai, Christopher; et al.
Abstract: Rationale: Integration of guidelines for severe asthma (SA) management into electronic medical records (EMRs) may greatly enhance asthma care and outcomes. Objectives: We aimed: 1) to develop an algorithm to identify SA patients in primary care EMRs using pan-Canadian standardized data elements and decision support that prompts adherence with best practice guidelines and 2) to develop EMR data standards for SA for use primarily by specialists. Methods: A draft algorithm and list of elements were prepared, based upon the Canadian Thoracic Society criteria for suspected SA, Pan-Canadian Respiratory Standards Initiative for Electronic Health Records (PRESTINE) Asthma and Chronic Obstructive Pulmonary Disease (COPD) Working Group Report and published SA registries. Using a modified Delphi process, a working group (WG) of 18 experts voted on algorithm steps, elements and data definitions. Consensus was defined a priori as ≥ 60%. The algorithm, data elements and definitions were revised based on external stakeholder review. Measurements and Main Results: The WG devised a 4-step algorithm to identify SA and identified minor revisions to PRESTINE Core asthma elements necessary for the algorithm. PRESTINE Core asthma elements were deemed Core for SA. The WG identified 108 Core and 48 Optional elements for SA. Of those, 26 Core elements and 15 Optional elements were unique to SA. Conclusions: An algorithm has been proposed that will identify SA patients in primary care EMRs based upon PRESTINE Core asthma elements. This initiative has also identified SA EMR elements for use primarily by specialists.